PSXV-8 Nutritional supplementation + testosterone treatment, increases, body weight, sexual odor, scrotal circumference and libido in male goats during sexual resting. - De Santiago-Miramontes, A (J Anim Sci, 2018)
The aim of this study was to evaluate the effect of nutritional supplementation + testosterone treatment, on Body Weight (BW), Body Condition Score (BCS) Sexual Odor (SO), Scrotal Circumference (SC) and sexual behavior of male goats in resting season in open range. This study was realized in Mexico (26°N, 104°W), using 12 males, divided into 2 groups (n=6 each; BCS 2.6 ± 0.57; BW 54 ± 13.9 kg). Group NST was fed only with native vegetation (4(th) January to 25(th) March 2017), while ST was fed with native vegetation plus 400 g of commercial concentrate (16% CP) and alfalfa (18% CP). Both groups received 25 mg of testosterone propionate, each third day/3 weeks (days 56–79). BW, BCS (scale 1–5), SO (scale 1–3) and SC (cm) were evaluated weekly (analyzed with ANOVA test; SAS 2002; experimental design of random blocks). On March 24(th) and 25(th), a sexual behavior test was performed. Each male was evaluated quantifying sexual behaviors (search and consummation), compared with a Chi-squared test; MYSTAT 12.There were differences between groups (P<0.001) in BW, ST: 66.50 ± 17.76, NST: 55.50 ± 11.88 kg, BC, SGT: 3.67 ± 0.63; NST: 2.38 ± 0.44, SC, ST: 30.00 ± 2.97, NST: 26.00 ± 3.59 cm, likewise there were difference in SO (P <0.05): ST: 1.17 ± 0.52, NST: 0.17 ± 0.41. Number of sexual search behaviors was lower in NST compared with ST (P<0.001; NST: 196 vs 2051 respectively), likewise, the number of consummatory sexual behaviors was lower in NST compared with ST (P<0.001; 7 vs 142 respectively). We conclude that a nutritional supplementation in grazing bucks treated with testosterone during the sexual resting increases the BW, BC, SO, and SC. Furthermore, a greater number of sexual behaviors can be substantial for the induction of reproductive performance in anovulatory female goats.